Extract Derived From Black Rice Functions as a Photothermal Agent for Suppressing Tumor Growth and Metastasis - Teng, Muzhou; Zhou, Shuyi; Zhang, Rongjun; Zhang, Yu; Xu, Yang; Fu, Xuemei (Frontiers in Bioengineering and Biotechnology, 2020)
It remains a challenge to develop an effective therapeutic agent with low cost and good biocompatibility for cancer therapy. Based on its dark color, we hypothesized that, the extraction from black rice grains, denoted BRE, could serve as a photothermal conversion agent. The results showed that BRE confers a high photothermal conversion efficiency up to 54.13%. The combination of BRE and near infrared (NIR) treatment enables effective photothermal tumor ablation, and suppress tumor metastasis via inhibiting the epithelial-mesenchymal transition (EMT) pathway. In addition, BRE exhibits no obvious toxicity in vivo. Therefore, BRE could serve as a promising photothermal therapy agent with a low toxicity to treat cancer.